Design and Development of Information System for Monitoring Files of Public Complaints at the Jakarta BPN Office - Robi Wahyu Ilahi; Sri Poedji Lestari; Bernadus Gunawan Sudarsono (Akademi Manajemen Informatika dan Komputer Widya Loka Medan, 2023)
The National Land Agency (BPN) is a non-ministerial government agency which is under and responsible to the President and led by the Head. The National Land Agency has the task of carrying out governmental tasks in the field of land nationally, regionally and sectorally in accordance with statutory provisions. In the management of monitoring files that are not centralized, the file management process is still manual, searching for files takes about an hour, and physical files have the potential to be lost or damaged. From the existing problems, an information system for monitoring community complaint files was designed and built which is expected to be able to handle these problems. For analysis and design methods use the Unfield Modeling Language (UML). This information system for monitoring public complaint files uses the programming language PHP and Mysql as the database. With this web-based information system for monitoring community complaint files, the processes involved in terms of monitoring are easier to use, accurate and integrated.